Revised administrative code of the Philippine Islands. 1934. Supplemental materials including acts, executive orders, and Constitution, 1934-1941 (U.S. Govt. Print. Off., 1945)
This compilation of Supplemental Materials to the Revised Administrative Code of the Philippine Islands of 1934 collects into a single volume all the important laws which amend, repeal or add to the 1934 code, and also the pertinent Executive Orders. The materials cover the period from the 1934 edition to the final work of the National Assembly prior to enemy occupation in 1941. For convenience, there is included the text of the Constitution of the Philippine Commonwealth of 1935, and amendments.